Study on the Characteristics and Formation Mechanism of Pressure Fluctuation in an Axial Flow Pump Based on Dynamic Mode Decomposition - Z. Y. Zhuang; H. H. Zhou; Z. Y. Yu (Journal of Applied Fluid Mechanics)
In this study, aiming at investigating the formation mechanism of pressure fluctuations of different frequencies in axial flow pumps, the characteristics of pressure fluctuation were determined using fast Fourier transform (FFT) on the basis of a numerical simulation of complex flow fields in the pump. The pressure and velocity modes corresponding to the primary pressure fluctuation frequency in the pump were decoupled and rebuilt using dynamic mode decomposition (DMD). The consequences showed that the primary pressure fluctuation frequencies in impeller were 11fn and 4fn and in diffuser were 4fn and 2fn, respectively, where fn is the shaft natural frequency. Moreover, the pressure fluctuation amplitude in diffuser was significantly larger than that in the impeller. DMD could identify the coherent structures of various frequency pressure fluctuations in the impeller and diffuser. In addition, the used method, which combines both FFT and DMD, revealed that the formation mechanisms of pressure fluctuations at different frequencies are different. In particular, the pressure fluctuation at 4fn in diffuser were caused by rotor–stator interaction (RSI) and flow separation near the suction surface (SS) of diffuser blades. Moreover, the pressure fluctuation at 2fn was caused by flow separation near the SS of diffuser blades and wake vortex shedding. In impeller, the pressure fluctuations at 11fn and 4fn resulted from RSI and flow separation at the leading edge (LE) of impeller blades, respectively.